(3TQM bUjOI GdEeGe GdLfjIs - (3GHf YLjHI , CMeO Hf eMeO Hf GdegOj GdMSfj GdGfLQj, CHh GdYHGS,J (B1224 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CVGA TYGY GdaLQ Yf Cab GdacQI CeG HYO abO SCdfi HYV GdENhGf Cf CTQM dg CHjGJkG ef cdGe Cgd GdYQaGf JfSH ddEeGe GdLfHI QVi Gddg Yfg s
(3BNQgG (B:s
(3hJfRgJ ai LfGJ GdUaGJ , hTGgOJgeG ai LejY GdJLdjGJ abO fVLJ GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B245 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B163s
Keywords: (3GdeLGejYs